1980
DOI: 10.1017/s0016672300019881
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive value of PGM polymorphism in laboratory populations ofDrosophila melanogaster

Abstract: Experiments have been performed to show that PGM polymorphism for the two common electrophoretic allozymes, PGM A and PGM B , in Drosophila melanogaster has adaptive value. Firstly, the allele frequencies converge to the same equilibrium value in six experimental populations. Secondly, density-dependent selection operates. Thirdly, the relative fitness of the three genotypes varies in modified culture media. PGM polymorphism is maintained by frequency-dependent selection and heterotic selection: the first mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The fact that this equilibrium applies at 18°C, 25°C and 29°C (Oakeshott, 1979;Carfagna et al, 1980) is also consistent with the geographic homogeneity of Pgm gene frequencies and their lack of consistent association with Tmax, but it contrasts with biochemical evidence indicating differences between the in vitro thermostabilities of respective Pgm allozymes. The thermostabilities of the Pgm12° and Pgm1'°° products appear to be greater than those of Pgm°70, although there are also indications of electrophoretically cryptic thermostability variants within Pgm oo (Trippa et al, 1978b;Fucci et al, 1979).…”
Section: Resultssupporting
confidence: 66%
“…The fact that this equilibrium applies at 18°C, 25°C and 29°C (Oakeshott, 1979;Carfagna et al, 1980) is also consistent with the geographic homogeneity of Pgm gene frequencies and their lack of consistent association with Tmax, but it contrasts with biochemical evidence indicating differences between the in vitro thermostabilities of respective Pgm allozymes. The thermostabilities of the Pgm12° and Pgm1'°° products appear to be greater than those of Pgm°70, although there are also indications of electrophoretically cryptic thermostability variants within Pgm oo (Trippa et al, 1978b;Fucci et al, 1979).…”
Section: Resultssupporting
confidence: 66%
“…Two patterns of results often obtained are the rapid elimination of the inversions from the populations and the restabilisation of the enzyme allele frequencies around values characteristic of the original wild-caught populations (e.g., Lewontin, 1958;Inoue, 1979;Carfagna et a!., 1980;PalabostCharles, 1982). Moreover, essentially the same results are often obtained in all the environments tested, despite the imposition of some relatively severe stresses, including , in relation to the enzymes, regimes which should impinge directly on the functions of the specific enzymes tested (e.g., extremes of substrate concentration; Zera et aL, 1983 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive differences have been found for a regulatory gene that controls PGM1 expression in the liver of rainbow trout, with faster developmental rates found for individuals that possess increased expression of PGM1 (Allendorf et al 1983). PGM polymorphisms in Drosophila melanogaster may be subject to balancing selection (Carfagna et al 1980;Oakshott et al 1985) and subsequent work has shown this gene to be evolving in an adaptive manner (Verrelli and Eanes 2000).…”
Section: Discussionmentioning
confidence: 96%